EXPERIMENTAL ENHANCEMENT OF SOLAR WATER HEATER FOR USING IN A LOW TEMPERATURE WITH HEAT EXCHANGER VERTICAL COLLECTOR BY CONCENTRATOR AND ACETONE - G. Mutasher, Dheya; Shakir Mahmood, Abdulrahman (Journal of Applied Engineering Science, 2025)
This study presents an innovative solar water heating system that integrates a condenser with water or acetone as the working fluid, offering a promising solution to key challenges in solar energy utilization, like cost efficiency, optimal angle alignment, and material limitations. The proposed design significantly improves thermal performance, making it a viable alternative to conventional flat-plate solar collectors. Experimental results demonstrate a significant efficiency improvement of 80% compared to conventional systems. This improvement is referred to two main factors: First, advanced collector geometry: The utilize of a spiral-coil tube design enhances radiation absorption in all directions, reducing dependence on precise solar angle alignment. Second, improved heat transfer fluid. where the acetone used as the working fluid due to its superior thermophysical properties significantly improves heat transfer rates within a thermosyphon-based natural circulation system. The efficiency of acetone was found to be higher in both the single- and double-loop cases by 77.66% and 70.78%, respectively, compared to water. The combination of these innovations ensures consistent energy capture and heat production, even under suboptimal conditions. Furthermore, the system's scalability and adaptability suggest it could be widely applied in engineering contexts, including residential, industrial, and agricultural heating. By addressing cost constraints and efficiency limitations, this spiral solar collector emerges as a revolutionary alternative to conventional solar thermal technologies, accelerating the adoption of renewable energy solutions.
Keywords: Solar water heater; Natural circulation flow; Thermosiphon system; Spiral coil tube; Acetone; Thermal efficiency